Trapping neutral fermions with kink-like potentials - de Castro, A. S.; Hott, M. (Elsevier B.V., 2006)
The intrinsically relativistic problem of neutral fermions subject to kink-like potentials (similar to tanh gamma x) is investigated and the exact bound-state solutions are found. Apart from the lonely hump solutions for E = +/- mc(2), the problem is mapped into the exactly solvable Sturm-Liouville problem with a modified Poschl-Teller potential. An apparent paradox concerning the uncertainty principle is solved by resorting to the concepts of effective mass and effective Compton wavelength. (c) 2005 Elsevier B.V. All rights reserved.